Labor analgesia with ropivacaine added to clonidine: a randomized clinical trial - Nakamura, Giane [UNESP]; Ganem, Eliana Marisa [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; Rugolo, Ligia Maria Suppo de Souza [UNESP]; Castiglia, Yara Marcondes Machado [UNESP] (Associação Paulista de Medicina (APM), 2008)
CONTEXTO E OBJETIVO: A associação entre ropivacaína e clonidina agiria menos que a ropivacaína isolada na mãe e no feto? Foram pesquisados os efeitos materno-fetais de duas técnicas farmacológicas: pequena dose de ropivacaína ou dose menor de ropivacaína mais clonidina na analgesia peridural para parto. TIPO DE ESTUDO E LOCAL: Estudo prospectivo, Departamento de Anestesiologia, Faculdade de Medicina de Botucatu, Universidade Estadual Paulista. MÉTODOS: Trinta e duas parturientes, estado físico de acordo com a American Society of Anesthesiologists I e II, foram aleatoriamente submetidas à analgesia peridural com 15 ml de ropivacaína 0,125% (grupo R) ou 15 ml de ropivacaína 0,0625% mais clonidina, 75 µg (grupo RC). Foram avaliados: intensidade da dor, nível do bloqueio sensitivo, latência, intensidade do bloqueio motor, duração da analgesia de parto e da analgesia peridural. Os neonatos foram avaliados pelo Apgar e método de Amiel-Tison (capacidade neurológica e adaptativa). RESULTADOS: Não houve diferenças significativas entre grupos para dor, nível de bloqueio sensitivo, duração da analgesia peridural e Apgar. Para latência, duração da analgesia de parto e bloqueio motor, grupo R < grupo RC. O escore da capacidade neurológica e adaptativa de meia e duas horas foi maior para o grupo R. Cem por cento dos neonatos do grupo R e 75% dos do grupo RC estavam neurologicamente saudáveis ao exame de 24 horas. CONCLUSÃO: Pequena dose de ropivacaína e dose menor mais clonidina aliviaram a dor materna durante o parto. Neonatos de mães que receberam apenas ropivacaína mostraram melhores escores da capacidade neurológica e adaptativa.

CONTEXT and OBJECTIVE: Previous studies have led to speculation that the association between ropivacaine and clonidine might be more effective than ropivacaine alone. We examined the maternal-fetal effects of two pharmacological approaches: a low dose of ropivacaine or a lower dose of ropivacaine plus clonidine for epidural analgesia during labor. DESIGN and SETTING: Prospective study at Department of Anesthesiology, Faculdade de Medicina de Botucatu, Universidade Estadual Paulista. METHODS: Thirty-two pregnant women in American Society of Anesthesiologists physical status I and II randomly underwent epidural analgesia using 15 ml of ropivacaine 0.125% (R group) or 15 ml of ropivacaine 0.0625% plus 75 µg clonidine (RC group). Pain intensity, sensory block level, latency time, motor block intensity, duration of labor analgesia and duration of epidural analgesia were evaluated. The newborns were evaluated using Apgar scores and the Amiel-Tison method (neurological and adaptive capacity score). RESULTS: There were no statistically significant differences between the groups regarding pain score, sensory block level, duration of epidural analgesia or Apgar score. The latency time, duration of labor analgesia and motor block were R group < RC group. The half-hour and two-hour neurological and adaptive capacity scores were higher in the R group. All of the R group newborns and 75% of the RC group newborns were found to be neurologically healthy at the 24-hour examination. RESULTS: There were no statistically significant differences between the groups regarding pain score, sensory block level, duration of epidural analgesia or Apgar score. The latency time, duration of labor analgesia and motor block were R group < RC group. The half-hour and two-hour neurological and adaptive capacity scores were higher in the R group. All of the R group newborns and 75% of the RC group newborns were found to be neurologically healthy at the 24-hour examination. CONCLUSION: Both low-dose ropivacaine and a lower dose plus clonidine relieved maternal pain during obstetric labor. Newborns of mothers who received only ropivacaine showed better neurological and adaptive capacity scores.
Analgesia de parto com ropivacaína associada à clonidina: pesquisa clínica randomizada
Keywords: Analgesia obstétrica; Anestesia epidural; Neonato; Anestésicos locais; Clonidina; Analgesia, obstetrical; Anesthesia, epidural; Infant, newborn; Anesthetics, local; Clonidine